A model of biased intermediation. (9th October 2019) - de Cornière, Alexandre; Taylor, Greg
Abstract: We study situations in which consumers rely on a biased intermediary's advice when choosing among sellers. We introduce the notion that sellers' and consumers' payoffs can be congruent or conflicting, and show that this has important implications for the effects of bias. Under congruence, the firm benefiting from bias has an incentive to offer a better deal than its rival and consumers can be better‐off than under no bias. Under conflict, the favored firm offers lower utility, and bias harms consumers. We study various policies for dealing with bias and show that their efficacy also depends on whether the payoffs exhibit congruence or conflict.